Validation of Wind Measurements From a 53 MHz ST Radar Pilot Array Located at University of Calcutta With Collocated Radiosonde Launches. Issue 3 (24th February 2022) - Nandakumar, P.; Jana, D.; Sunilkumar, S. V.; Satheesh Chandran, P. R.; Vishnu, R.; Das, T.; Emmanuel, Maria; Singh, G.; Majumder, S.; Siddiqui, J. Y.; Paul, A.
Abstract: A Stratosphere‐Troposphere (ST) Radar operating at 53 MHz is being installed at Ionosphere Field Station (22.94°N, 88.51°E, and 34°N geomagnetic latitude) of University of Calcutta in the eastern part of India adjoining northern Bay of Bengal. This radar is unique, being the only one operational at this frequency in the entire eastern and northeastern part of the country and also in the south‐east Asian longitude sector. Two components of horizontal winds (zonal and meridional) measured by the Pilot version of this radar have been validated with 90 collocated simultaneous balloon‐borne radiosonde observations during July and August 2019. A good correlation of the order of 90%–99% and 75%–95% up to 8 km has been observed between the radar and radiosonde measured zonal winds and meridional winds respectively. This correlation is much stronger between 2 and 6 km altitudes. The correspondence is better for the zonal winds than meridional. However, there have been some data outliers, which may primarily be attributed to different measurement techniques, large beam width of the Pilot array and less antenna aperture. The differences between radar and radiosonde measurements are marginally higher for precipitation events compared to non‐precipitation cases. The zonal and meridional wind patterns exhibit different variations in July and August 2019 while the standard errors in zonal and meridional winds mostly lie within 1 m/s. These results are the first validation of the Pilot version of this radar facility. Plain Language Summary: A 53 MHz radar is being set up by University of Calcutta near Calcutta in the geophysically sensitive transition region from the tropics to the sub‐tropics in the eastern part of India adjoining Bay of Bengal. It is designed to measure atmospheric winds, which could be very severe particularly during tropical cyclones which often affect this region. As an initial step, a Pilot version of the radar has been established and wind measurements compared with simultaneous collocated balloon‐borne radiosondes during July‐August 2019 for precipitation as well as non‐precipitation days up to altitudes of 8 km. Good correspondence have been noted between the two measurements with 90% correlation. Some data outliers have been noted which may be due to large beam width of the Pilot system and less antenna aperture. Key Points: Validation of zonal and meridional wind measurements using a Stratosphere‐Troposphere Radar with radiosondes during July‐August 2019 Good correspondence of about 90% is noted between the two measurements Validation has been classified into precipitation and non‐precipitation cases up to 8 km height